Temperature and dehydration effects on metabolism, water uptake and the partitioning between respiratory and cutaneous evaporative water loss in a terrestrial toad - Senzano, Luis Miguel [UNESP]; Andrade, Denis Vieira [UNESP] (Company Biologists Ltd, 2018)
Terrestrial anurans often experience fluctuations in body temperature and hydration state, which are known to influence evaporative water loss through the skin (EWLSkin) and lungs (EWLResp). These effects arises from associated changes in skin permeability, metabolism and lung ventilation. Herein, we determined the rates of EWLSkin and EWLResp in the terrestrial toad, Rhinella diptycha at different temperatures and hydration states. We measured oxygen uptake rates to verify whether alterations in the partitioning between EWLSkin and EWLResp were associated to metabolic induced changes in pulmonary gas exchange. We also measured the influence of hydration and temperature on water uptake (WU) through the skin. Finally, since estimates of skin resistance to evaporation (R-s) are usually inferred from total evaporative water loss (EWLTotal), under the assumption of negligible EWLResp, we calculate the potential error in accepting this assumption, under different temperature and hydration states. EWLSkin and EWLResp increased with temperature, but this response was greater for EWLResp, which was attributed to the temperature-induced elevation in metabolism and lung ventilation. Dehydration caused a decrease in the relative contribution of EWLSkin to EWLTotal, mirrored by the concurrent increase in the contribution of EWLResp, at all temperatures. Thus, R-s increased with dehydration. WU rates were dictated by dehydration with little influence of temperature. The partitioning between EWLSkin and EWLResp was affected by both temperature and hydration state and, under some set of conditions, considering EWLResp as negligible led to significant errors in the assessment of skin resistance to evaporation.
Keywords: Amphibians; Anurans; Thermoregulation; Water balance; Skin resistance; Oxygen uptake